Bulk Photovoltaic Effect in 2D Materials for Solar‐Power Harvesting. Issue 23 (12th September 2022) - Aftab, Sikandar; Iqbal, Muhammad Zahir; Haider, Zeeshan; Iqbal, Muhammad Waqas; Nazir, Ghazanfar; Shehzad, Muhammad Arslan
Abstract: It is highly desirable for exploring and discovering new materials and outcome‐based approaches to exceed the Shockley–Queisser limit for single‐junction photovoltaic cells. Low‐dimensional piezoelectric materials have the potential to generate the optoelectronic phenomenon called the bulk photovoltaic effect, which is not limited by the theoretical limit for solar radiation into electricity conversion. The recent development of 2D materials has demonstrated that by using the bulk photovoltaic effect (BPVE) for crystals lacking inversion symmetry, it is possible to overcome this limit. So far, the exploration of p–n junction designs has been addressed in several review articles. However, the mechanism of BPVE differs from traditional p–n junction‐based photovoltaics in 2D materials. In this focused review, various concepts regarding the shift‐current response are explored, both from theoretical and experimental points of view, which are generated in the framework of deformed 2D materials. Finally, prospective approaches for building BPVE‐based next‐generation solar cells using ultrathin 2D materials are presented. These materials are expected to work better than current methods of turning energy into electricity. Abstract : Exceeding the Shockley–Queisser limit for single‐junction photovoltaic cells is highly desirable for exploring and discovering new materials and outcome‐based approaches. When the threefold rotational and mirror symmetry of 2D material devices is broken by strain‐gradient engineering, induced polarization in van der Waals interfaces, or transforming a 2D monolayer into a nanotube, shift‐current responses are enabled.